2014
DOI: 10.12659/aot.890125
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for kidney allograft survival in the Eurotransplant Senior Program

Abstract: Risk reduction (e.g., aiming at CIT <15 h) and close surveillance of patients at risk appear to be crucial for allograft survival in the ESP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
14
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 0 publications
4
14
1
Order By: Relevance
“…In these studies, patient and graft survival were comparable to our own results. Primary non-function seems to be high in our cohort (10.8%) but has also been observed in other ESP cohorts with similar rates ranging from 7.3% to 10.1% [ 11 14 ].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In these studies, patient and graft survival were comparable to our own results. Primary non-function seems to be high in our cohort (10.8%) but has also been observed in other ESP cohorts with similar rates ranging from 7.3% to 10.1% [ 11 14 ].…”
Section: Discussionsupporting
confidence: 87%
“…On the other hand, the risk of acute rejection has to be considered. In our patients, BPAR of 13.5% was quite low compared to other ESP cohorts, which had rates of BPAR ranging up to 37% [ 11 14 ]. Still, in our ESP patients, it was a relevant factor accounting for graft loss in 10.8% of the patients in the first year after transplantation.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…We set the timing of treatment at three hours in order to keep the CIT as short as possible, due to its relation to organ dysfunction and survival [ 47 , 48 ]. Additionally, in our preliminary experiments, longer treatment times were not associated with better features of kidneys in terms of metabolic activity and tissue damage (data not reported).…”
Section: Discussionmentioning
confidence: 99%
“…However, the development of hematomas or bleeding episodes after ABOi RTx is rarely reported by centers using PPh or double filtration plasmapheresis and prevalence seems to be low with <5% [ 8 , 28 , 30 ]. Several studies showed that the overall surgical complication rate was higher in ABOi RTx patients than in ABOc RTx patients [ 27 , 31 ], with hematomas being the most frequently observed complication. In our study, surgical complications were not correlated with the use of a specific IA column which is in accordance to the data from Morath at al.…”
Section: Discussionmentioning
confidence: 99%